Decoupling the metal–insulator transition temperature and hysteresis of VO2 using Ge alloying and oxygen vacancies. Issue 46 (13th May 2022) - Schofield, Parker; Braham, Erick J.; Zhang, Baiyu; Andrews, Justin L.; Drozdick, Hayley K.; Zhao, Dexin; Zaheer, Wasif; Gurrola, Rebeca M.; Xie, Kelvin; Shamberger, Patrick J.; Qian, Xiaofeng; Banerjee, Sarbajit
Abstract : Ge alloying enables independent control of forward and reverse metal–insulator transitions in VO2, enabling decoupling of transformation-temperature and hysteresis. Abstract : The metal-to-insulator transition of VO2 underpins applications in thermochromics, neuromorphic computing, and infrared vision. Ge alloying is shown to elevate the transition temperature by promoting V–V dimerization, thereby expanding the stability of the monoclinic phase to higher temperatures. By suppressing the propensity for oxygen vacancy formation, Ge alloying renders the hysteresis of the transition exquisitely sensitive to oxygen stoichiometry.